PERANAN IKLAN DALAM MEMPENGARUHI MINAT ORANG TUA MEMILIH BIMBINGAN BELAJAR ANDRESSEMPOA DI BANDAR LAMPUNG - Yohannes P Kumagaya (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2013)
Advertising is one of the instruments of modern marketing activities based on the concept ofcommunication, then the consumer will pay attention to, understand, interpret Andres pond to thoseads that generate interest to make a purchase.From the data analysis and testing hypotheses about the Role of Advertising to AffectParents interest Choosing Andre Sempoa Tutoring in Bandar Lampung: The amount of interest inrelation to the advertisement Parents Choosing Andre Sempoa Tutoring in Bandar Lampung is0,703. The magnitude of the effect can be seen from the magnitude of the coefficient ofdetermination(R2) of 0.494, which means 49.4% of the interest in the Parent Choosing AndreSempoa Tutoring can be Affected by variables ads.Statistical tests indicated by the value t count > t table value or t statistic 7.197 >tstatistictable1.68. Thus Ho: rejected and Haaccepted. It can be concluded that there is in deed asignificant difference between the interest ad Parents Choosing Andre Sempoa tutoring in BandarLampung.